Understanding Land and Building Tax Compliance Through Tax Knowledge, Taxpayer Income, and Government Trust - Monika Budiman; Marini Anggie Putri Siregar; Aang Syahdina; Malik Hidayat; Dhevia Pragatti (Jurnal Riset Akuntansi dan Auditing, 2026)
This study examines the effects of tax knowledge, taxpayer income, and trust in government on taxpayer compliance in paying land and building tax (PBB). The population consisted of 41,375 land and building tax objects in Koja District, North Jakarta. Using incidental sampling and the Slovin formula, a sample of 100 respondents was obtained, resulting in 100 observations analyzed in this study. Data were analyzed using smartPLS 4.0. The novelty of this research lies in investigating the combined effects of tax knowledge, taxpayer income, and trust in government on land and building tax compliance within a specific regional context using the smartPLS approach. The results indicate that tax knowledge and taxpayer income have a positive and significant effect on taxpayer compliance, whereas trust in government has no significant effect. The findings imply that the Directorate General of Taxes should strengthen taxpayer education through seminars, direct outreach programs, and accessible online campaigns. Compliance strategies may also be tailored to taxpayers’ income levels through educational support and incentives for lower-income groups, as well as stronger law enforcement for higher-income groups. Overall, efforts to improve compliance should emphasize educational and technical approaches rather than relying solely on enhancing the government's public image. Abstrak - Penelitian ini bertujuan untuk menguji pengaruh pengetahuan perpajakan, pendapatan wajib pajak, dan kepercayaan terhadap pemerintah terhadap kepatuhan wajib pajak dalam membayar pajak bumi dan bangunan (PBB). Populasi penelitian terdiri atas 41.375 objek pajak bumi dan bangunan di Kecamatan Koja, Jakarta Utara. Teknik pengambilan sampel menggunakan incidental sampling dengan rumus Slovin sehingga diperoleh 100 responden, dengan total 100 observasi yang dianalisis dalam penelitian ini. Analisis data dilakukan menggunakan smart-PLS 4.0. Kebaruan penelitian ini terletak pada pengujian secara simultan pengaruh pengetahuan perpajakan, pendapatan wajib pajak, dan kepercayaan terhadap pemerintah terhadap kepatuhan PBB dalam konteks wilayah tertentu dengan pendekatan smart-PLS. Hasil penelitian menunjukkan bahwa pengetahuan perpajakan dan pendapatan wajib pajak berpengaruh positif dan signifikan terhadap kepatuhan wajib pajak, sedangkan kepercayaan terhadap pemerintah tidak berpengaruh signifikan. Implikasi penelitian menunjukkan bahwa Direktorat Jenderal Pajak perlu memperkuat edukasi perpajakan melalui seminar, sosialisasi langsung, dan kampanye daring yang mudah diakses. Strategi peningkatan kepatuhan juga dapat disesuaikan dengan tingkat pendapatan wajib pajak melalui edukasi dan insentif bagi kelompok berpendapatan rendah serta penguatan penegakan hukum bagi kelompok berpendapatan tinggi. Secara keseluruhan, peningkatan kepatuhan wajib pajak perlu lebih difokuskan pada pendekatan edukatif dan teknis dibandingkan hanya pada peningkatan citra pemerintah.